2020
DOI: 10.1111/scd.12460
|View full text |Cite
|
Sign up to set email alerts
|

Dental services provided to Syrian refugee children in Jordan: A retrospective study

Abstract: Background:Little is known about oral health care in Syrian refugee children in host countries. We describe the pattern and nature of oral healthcare service provided to Syrian refugee children in Jordan Method: The clinical records of 3 to 7-year-old children who attended dental clinics at Zaatari refugee camp over a period of 8 months were retrieved and analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
51
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(60 citation statements)
references
References 40 publications
(45 reference statements)
7
51
0
Order By: Relevance
“…Refugees are more susceptible to a variety of illnesses, including dental problems [ 23 ]. Latest reports have shown that refugees have a higher incidence of dental caries and impaired oral hygiene than host people [ 2 4 ]. Untreated dental diseases can result in tooth decay/loss, which can lead to unhealthy eating habits and a decline in quality of life [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Refugees are more susceptible to a variety of illnesses, including dental problems [ 23 ]. Latest reports have shown that refugees have a higher incidence of dental caries and impaired oral hygiene than host people [ 2 4 ]. Untreated dental diseases can result in tooth decay/loss, which can lead to unhealthy eating habits and a decline in quality of life [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Refugee children are particularly vulnerable to oral diseases [ 4 ]. Malocclusion is a common oral health problem, after tooth decay and periodontal disease, and is ranked third in dental public health priorities worldwide [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study found that most elements under human and physical health resources range from acceptable to very satisfied, except for ‘ease of access to general/oral health facilities’ and ‘availability of all dental services’. It has been reported previously that the attitude of non-attendance or delays in obtaining dental/medical treatment are strongly associated with accessibility, income, availability of healthcare facilities and perception of the need for routine dental care; all of which are major concerns for the refugee population [ 7 , 26 ]. Furthermore, extended waiting times for emergency and routine dental treatment are associated with higher rates of amplified deterioration of teeth [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, extended waiting times for emergency and routine dental treatment are associated with higher rates of amplified deterioration of teeth [ 27 ]. All of the factors listed above result in delay in pursuing dental care, and therefore leading to an extraordinary percentage of dental extractions [ 7 , 26 ]. Consequently these two elements have negative and irreversible consequences on the health of this population, warranting an effective and targeted service with increased capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation